Survey of Location Sensing Techniques - Joshi, Abhash (Journal on Geoinformatics, Nepal, 2017)
Location-based services (LBS) have wide applicability in areas like navigation, tracking, emergency services, gaming, persuasive applications etc. The core element of any LBS is its positioning technology. This paper reviews taxonomy of location sensing techniques. Then several location sensing techniques like Global positioning system, Visible light positioning, Cell-Id, Received signal strength, Image recognition and IP based geolocation is surveyed,summarized and classified. Finally, this paper identifies the similarity and differences in location sensing techniques, current research trends and also area for future study.